Heavy metal contamination assessment and modeling of fate and transport of mercury in Bued river - Orozco, Christian R. (College of Engineering, University of the Philippines Diliman, 2014)
In the Philippines, there has been a growing concern on the consequences of the activities of mineral exploration and extraction. Wastewater from mining industries may contain heavy metals that are toxic to the environment such as mercury (Hg), lead (Pb) and Arsenic (As). Water bodies nearby mining sites like the Bued River are especially at risk of heavy metal contamination. In this study, assessment of heavy metal contamination and modeling of fate and transport of Hg in Bued River were performed. Physico-chemical characteristics were measured in 14 sampling points along Bued River. Wastewater samples were collected and characterized. Concentrations of Hg, Pb and As in both the sediment and water column samples were determined in laboratory using cold vapor atomic absorption spectroscopy (AAS), flame AAS and hydride generation AAS respectively. Significantly higher concentrations of Hg, PB and As were observed in sediment compared to water samples especially in areas near mining operations. Maximum measured values of Pb (2646.24 mg/kg) and As (30.47 mg/kg) in sediments exceeding that of the toxic effects threshold of the Canada sediment quality guidelines while maximum Hg (0.373 mg/kg) measurement exceeded that of the minimal effects threshold for a downstream distance of 3.4km. This indicates that heavy metals in Bued River may pose low to medium risk to the environment. In wastewater samples from small-scale mining in Bued River, elevated values of mercury concentrations were observed. Modeling of fate and transport of mercury in Bued River as carried out by coupling a Geographical Information System (GIS) hydrologic model (HEC-HMS) with a contaminant transport model (WASP). Digital elevation model (DEM) of Bued watershed was used to determine drainage networks from drainage paths and watershed boundaries. Hydrologic simulations were performed using daily precipitation data. Results of the simulated flows were found were found to be in good agreement with that of the observed data (R2=0.8322, PBIAS=0.159). Contaminant model was able to simulate solids and mercury species such as total mercury, divalent mercury and methylmercury in the water column and sediments under different hydrological regimes. Because of affinity of mercury in sediments, periods of high flows showed high concentration of total mercury in water due to resuspension of particles. The transport of mercury in Bued River was found to be governed by flow and total suspended solids